Feasibility of Systems Support Mapping to guide patient-driven health self-management in colorectal cancer survivors. Issue 5 (4th May 2023) - Sohl, Stephanie J.; Befus, Deanna; Tooze, Janet A.; Levine, Beverly; Golden, Shannon L.; Puccinelli-Ortega, Nicole; Pasche, Boris C.; Weaver, Kathryn E.; Lich, Kristen Hassmiller
Abstract: Objective: To evaluate feasibility of System Support Mapping (MAP), a systems thinking activity that involves creating a diagram of existing self-management activities (e.g. symptom management, health behaviors) to facilitate autonomous engagement in optimal self-management. Design: One-arm pilot study of MAP in colorectal cancer survivors (NCT03520283). Main outcome measures: Feasibility of recruitment and retention (primary outcome), acceptability, and outcome variability over time. Results: We enrolled 24 of 66 cancer survivors approached (36%) and 20 completed follow-up (83%). Key reasons for declining participation included: not interested ( n = 18), did not perceive a need ( n = 9), and emotional distress/overwhelmed ( n = 7). Most participants reported that MAP was acceptable (e.g. 80% liked MAP quite a bit/very much). Exploratory analyses revealed a −4.68 point reduction in fatigue from before to 2 weeks after MAP exceeding a minimally important difference ( d = −0.68). There were also improvements in patient autonomy ( d = 0.63), self-efficacy (for managing symptoms: d = 0.56, for managing chronic disease: d = 0.44), psychological stress ( d = −0.45), anxiety ( d = −0.34), sleep disturbance ( d = −0.29) and pain ( d = −0.32). Qualitative feedback enhanced interpretation of results. Conclusions: MAP feasibility in colorectal cancer survivors was mixed, predominantly because many patients did not perceive a need for this approach. MAP was acceptable among participants and showed promise for improving health outcomes.